2014
DOI: 10.1111/tpj.12664
|View full text |Cite
|
Sign up to set email alerts
|

An O‐methyltransferase modifies accumulation of methylated anthocyanins in seedlings of tomato

Abstract: SUMMARYAnthocyanins contribute to the appearance of fruit by conferring to them a red, blue or purple colour. In a food context, they have also been suggested to promote consumer health. In purple tomato tissues, such as hypocotyls, stems and purple fruits, various anthocyanins accumulate. These molecules have characteristic patterns of modification, including hydroxylations, methylations, glycosylations and acylations. The genetic basis for many of these modifications has not been fully elucidated, and nor ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…Plant OMTs are a large gene family, which are categorized into two types, COMT and CCoAOMT, according to their molecular weight and bivalent ion dependency. In plants, numerous OMT genes have been identified, and their functions have been extensively investigated in various plant species, such as Arabidopsis 39 , barley 40 , mango 41 , rice 42 , tomato 43 , and sweet basil 44 . In citrus, it was reported that 58 OMT genes existed and were unevenly distributed on the nine chromosomes of Citrus sinensis.…”
Section: Discussionmentioning
confidence: 99%
“…Plant OMTs are a large gene family, which are categorized into two types, COMT and CCoAOMT, according to their molecular weight and bivalent ion dependency. In plants, numerous OMT genes have been identified, and their functions have been extensively investigated in various plant species, such as Arabidopsis 39 , barley 40 , mango 41 , rice 42 , tomato 43 , and sweet basil 44 . In citrus, it was reported that 58 OMT genes existed and were unevenly distributed on the nine chromosomes of Citrus sinensis.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the mass spectrum of peak 8 with a retention time at 16 (trans-p-coumaroyl)-5-O-glucoside. The peak 15 with retention time at 32.68 min that had a molecular ion and fragment of 963.2803 and 317 [Pt]+ corresponded to a petunidin aglycone, which was tentatively identified as petunidin-3-(feruloyl)-rutinoside-5-glucoside [21][22][23]. Finally, the peak 17 with a retention time at 36.54 min was identified as malvidin-3-(feruloyl)-rutinoside…”
Section: Identification Of Anthocyanins In the Atpap1-overexpressed Bmentioning
confidence: 99%
“…The recombinant enzyme methylated flavones and flavonols in the meta -position, while it methylated dihydroflavones and dihydroflavonols in the para -position, and the role of a single amino acid required for the conversion of para to meta was verified by incubating substrates with the CCoAOMT7 wild type and CCoAOMT7 single mutant, respectively ( Wils et al , 2013 ). In addition, CCoAOMT-like enzymes involved in the methylation of anthocyanins have been functionally characterized in vivo and vitro , including VvAOMT from Vitis vinifera ( Hugueney et al , 2009 ), SlAnthOMT from Solanum lycopersicum ( Gomez Roldan et al , 2014 ), and PsAOMT from Paeonia suffruticosa cv. ‘Gunpohden’ ( Du et al , 2015 ).…”
Section: Introductionmentioning
confidence: 99%